An ethnographic person-centered study of leadership development in high school basketball team captains. Issue 3 (2nd September 2017) - Mead, Jason; Gilson, Todd A.; Henning, Mary Beth
ABSTRACT: Using Kouzes and Posner's (2002. The leadership challenge (3rd ed.). San Francisco, CA: Jossey-Bass) Five Exemplary Practices of Leadership as a framework, four captains of a high school boys' basketball team participated in a qualitative person-centered ethnography regarding their perceptions of leadership development over the course of a season. The study found that the captains each perceived improvement in their use of voice in leadership situations, and not much improvement in other self-defined specific leadership areas. The captains also perceived that their improvement was a maturation process driven by necessity and precipitated by observation, personal experience, mentoring and coaching, and increased confidence. Finally, captains described hindrances to their leadership, including personal circumstances and difficult teammates. Implications of these findings for athletic coaches are discussed, including specific ideas for providing mentoring and instruction for team captains and other team members.